2021
DOI: 10.3389/fphar.2021.627032
|View full text |Cite
|
Sign up to set email alerts
|

The Balance of MU-Opioid, Dopamine D2 and Adenosine A2A Heteroreceptor Complexes in the Ventral Striatal-Pallidal GABA Antireward Neurons May Have a Significant Role in Morphine and Cocaine Use Disorders

Abstract: The widespread distribution of heteroreceptor complexes with allosteric receptor-receptor interactions in the CNS represents a novel integrative molecular mechanism in the plasma membrane of neurons and glial cells. It was proposed that they form the molecular basis for learning and short-and long-term memories. This is also true for drug memories formed during the development of substance use disorders like morphine and cocaine use disorders. In cocaine use disorder it was found that irreversible A2AR-D2R com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Also by the observation that A2AR mediated synaptic depression was counteracted not only by an A2AR antagonist but also by a dopamine D2R antagonist. This can be explained by the fact these two receptors are primarily located in the dorsal and ventral striatal pallidal GABA neurons mediating motor inhibition and antireward, respectively ( Borroto-Escuela et al, 2021a ; Borroto-Escuela et al, 2021b ).…”
Section: Understanding the Mechanisms For A2ar Mediated Activation Of Step: Involvement Of A2ar Heterocomplexesmentioning
confidence: 99%
See 3 more Smart Citations
“…Also by the observation that A2AR mediated synaptic depression was counteracted not only by an A2AR antagonist but also by a dopamine D2R antagonist. This can be explained by the fact these two receptors are primarily located in the dorsal and ventral striatal pallidal GABA neurons mediating motor inhibition and antireward, respectively ( Borroto-Escuela et al, 2021a ; Borroto-Escuela et al, 2021b ).…”
Section: Understanding the Mechanisms For A2ar Mediated Activation Of Step: Involvement Of A2ar Heterocomplexesmentioning
confidence: 99%
“…The D2R activation markedly inhibits the firing of these two types of neurons via its inhibitory Gi/o coupling of the D2R, causing increases in motor activity and reductions of anti-reward. The striatal-pallidal GABA neurons are enriched in A2AR-D2R heterocomplexes in which the activated A2AR protomer strongly blocks the D2R protomer mediated signaling through allosteric inhibition of the D2R protomer ( Borroto-Escuela et al, 2021b ) ( Figure 1 ). It should be noted that the work of the Italian group in 2020 takes place in striatum, which may be further defined as to the possible inclusion also of the ventral striatum or if it only involved the dorsal striatum.…”
Section: Understanding the Mechanisms For A2ar Mediated Activation Of Step: Involvement Of A2ar Heterocomplexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, preclinical studies indicate significant interactions between type 1 cannabinoid receptors (CB1R) and adenosine A2 receptors (A2AR). Both CB1R and A2AR are highly expressed in the striatum, and multiple studies have demonstrated that CB1R and A2AR can form heterodimers [ 13 ]. There is functional evidence for interactions between the two systems; for example, the hypolocomotor and rewarding effects of CB1R agonists are diminished by A2AR antagonism [ 14 ].…”
Section: Introductionmentioning
confidence: 99%